Prediction of Active Compounds From Annona Muricata Leaves As Inhibitors of the Wdr5–Myc Interaction in Breast Cancer Through A Molecular Docking Approach - Tedjo, Aryo; Yantih, Novi; Fadilah, Fadilah; Rafi, Mohamad (Devotion : Journal of Research and Community Service, 2026)
Breast cancer is one of the malignancies with a high morbidity rate, in which the excessive activation of the Myc proto-oncogene protein (MYC) plays a critical role in tumor proliferation and progression. MYC requires the presence of WD repeat-containing protein 5 (WDR5) to bind to its target genes; thus, the WDR5–MYC interaction represents a strategic target for the development of breast cancer therapy. This study aimed to identify leaf metabolites of Annona muricata with the potential to inhibit the WDR5–MYC interaction using an in silico approach. A total of 193 metabolites from the KNApSAcK database were modeled in 3D and analyzed by molecular docking using Molegro Virtual Docker (MVD) against the structure of WDR5 in complex with a MYC inhibitor fragment (PDB ID: 6UHY). Docking validation was performed by redocking the native ligand, 1-cyclohexyl-1H-benzimidazole-5-carboxylic acid, which yielded an RMSD value < 2 Å. The docking results indicated that epicatechin gallate, muricatetrocin B, and isoorientin exhibited the highest binding affinities, with Moldock Scores of –123.522, –115.862, and –97.3305 kJ/mol, respectively, supported by strong hydrogen-bond interactions. Interaction visualization revealed that epicatechin gallate formed more key interactions with critical residues in the WDR5 active site compared with the native ligand. These findings suggest that epicatechin gallate is a promising candidate for inhibiting the WDR5–MYC interaction and may be further developed as a natural-product-based anticancer agent.